Farmers on the frontline: Extreme weather events, mental health, preparedness and adaptation in an Australian sample - Kylie Rice; Tonelle Handley; Emma Austin; Adam J. Rock; Anthony S. Kiem; Rebecca Patrick; Caryn West; Yumiko Coffey; Alison Kennedy; Kim Usher (Journal of Rural Studies, 2026)

Learn to listen and listen to learn: reflections from a co-production process between researchers and composers - Carolin Seiferth; Agnes B. Olin; Konstantinos-Marios Vaziourakis; Sriharsha Bhat; Åsa N. Austin; Christina Lin; Sampo Kasurinen; Zacharias Ehnvall; Mioko Yokoyama; Maya Miro Johnson; Anna Berg; David Tudén; et al. (Sustainability Science, 2026)
As platforms for dialogue, art-science collaborations hold the potential to cross disciplinary boundaries to better understand and engage the public in addressing sustainability challenges. Moving beyond documenting outcomes, this study details how researchers and composers combined science communication and artistic expression to co-produce performances as part of the Baltic Sea Festival Science Lab. Drawing on insights from a joint reflection process, we recount our motivations for participation, provide insights on the co-production processes of six researcher-composer pairs, and share our experiences of the performances. We highlight openness to other ways of working, different perspectives and opinions, and emergence as well as collaborative skills, including listening, communication, and problem-solving skills, as key enablers for crossing disciplinary boundaries in art-science collaborations. As answers to the question on how, why, and in what ways platforms for dialogue can turn into platforms for learning, we discuss opportunities for designing safe-enough spaces, working towards a shared goal while embracing the unfolding nature of a process, and engaging in reflection to follow up on and make sense of one’s learning. Through this study, we hope to provide guidance for those who wish to engage in art-science collaborations to co-produce pathways towards sustainable futures together.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Protecting child nutrition and fishery ecosystems: A cluster controlled trial in coastal Kenya - Lora L. Iannotti; Andrew Wamukota; Elizabeth Kamau-Mbuthia; Carolyn Lesorogol; Ivy Blackmore; Lisa Sherburne; Catherine Sarange; Francis Mbogholi; Clay Obata; Christopher Cheupe; Joaquim Cheupe; Emma Strand; et al. (Global Food Security, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Scale-dependent topographic complexity underpins abundance and spatial distribution of ecosystem engineers on natural and artificial structures - Franz Bauer; Antony M. Knights; John N. Griffin; Mick E. Hanley; Andy Foggo; Austin Brown; Emma Jones; Louise B. Firth (Science of The Total Environment, 2024)

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

A comparative review of the toxicity mechanisms of perfluorohexanoic acid (PFHxA) and perfluorohexanesulphonic acid (PFHxS) in fish - Mark Kreychman; Emma Ivantsova; Austin Lu; Joseph H. Bisesi; Christopher J. Martyniuk (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Occurrence and toxicity mechanisms of perfluorobutanoic acid (PFBA) and perfluorobutane sulfonic acid (PFBS) in fish - Emma Ivantsova; Austin Lu; Christopher J. Martyniuk (Chemosphere, 2024)

A comparative review and computational assessment of acetochlor toxicity in fish: A novel endocrine disruptor? - Austin Lu; Emma Ivantsova; Christopher J. Martyniuk (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Cultivation and characterization of snowbound microorganisms from the South Pole - Mackenzie K. Hayward; Emma D. Dewey; Kathryn N. Shaffer; Austin M. Huntington; Brad M. Burchell; Lynn M. Stokes; Brittney C. Alexander; Janessa E. George; Megan L. Kempher; Samantha B. Joye; Michael T. Madigan; W. Matthew Sattley (Extremophiles, 2021)

Internal waves influence the thermal and nutrient environment on a shallow coral reef - Emma C. Reid; Thomas M. DeCarlo; Anne L. Cohen; George T. F. Wong; Steven J. Lentz; Aryan Safaie; Austin Hall; Kristen A. Davis (Limnology and Oceanography, 2019)
Internal waves can influence water properties in coastal ecosystems through the shoreward transport and mixing of subthermocline water into the nearshore region. In June 2014, a field experiment was conducted at Dongsha Atoll in the northern South China Sea to study the impact of internal waves on a coral reef. Instrumentation included a distributed temperature sensing system, which resolved spatially and temporally continuous temperature measurements over a 4‐km cross‐reef section from the lagoon to 50‐m depth on the fore reef. Our observations show that during summer, internal waves shoaling on the shallow atoll regularly transport cold, nutrient‐rich water shoreward, altering near‐surface water properties on the fore reef. This water is transported shoreward of the reef crest by tides, breaking surface waves and wind‐driven flow, where it significantly alters the water temperature and nutrient concentrations on the reef flat. We find that without internal wave forcing on the fore reef, temperatures on the reef flat could be up to 2.0°C ± 0.2°C warmer. Additionally, we estimate a change in degree heating weeks of 0.7°C‐weeks warmer without internal waves, which significantly increases the probability of a more severe bleaching event occurring at Dongsha Atoll. Furthermore, using nutrient samples collected on the fore reef during the study, we estimated that instantaneous onshore nitrate flux is about four‐fold higher with internal waves than without internal waves. This work highlights the importance of internal waves as a physical mechanism shaping the nearshore environment, and likely supporting resilience of the reef.